2020
DOI: 10.3390/ma13071771
|View full text |Cite
|
Sign up to set email alerts
|

Prototype Gastro-Resistant Soft Gelatin Films and Capsules—Imaging and Performance In Vitro

Abstract: The following study is a continuation of the previous work on preparation of gastro-resistant films by incorporation of cellulose acetate phthalate (CAP) into the soft gelatin film. An extended investigation on the previously described binary Gelatin-CAP and ternary Gelatin-CAP-carrageenan polymer films was performed. The results suggest that the critical feature behind formation of the acid-resistant films is a spinodal decomposition in the film-forming mixture. In the obtained films, upon submersion in an ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The next three papers are devoted to the ever-expanding technological approaches in solid oral dosage forms like tablets [ 7 , 8 ] and capsules [ 9 ]. Jamróz et al focus on the deep analysis of the relationship between structure and pharmaceutical characteristics in 3D printed tablets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The next three papers are devoted to the ever-expanding technological approaches in solid oral dosage forms like tablets [ 7 , 8 ] and capsules [ 9 ]. Jamróz et al focus on the deep analysis of the relationship between structure and pharmaceutical characteristics in 3D printed tablets.…”
mentioning
confidence: 99%
“…It was shown that this process affected particle size and shape, improved the in vitro bicalutamide release profile, and it evoked changes in the drug crystallinity. The paper by Maciejewski et al [ 9 ] provides data on the gastro resistant soft gelatin films and capsule formulation from binary-gelatin/cellulose acetate phthalate and ternary-gelatin/cellulose acetate phthalate/carrageenan films. They suggest that the discreet kinetically-limited phase separation was the crucial factor affecting the disintegration of the films.…”
mentioning
confidence: 99%